Peran Literatur Arab dalam Pengembangan Penyiaran Dakwah Islam - Burhanuddin; Adi Gunawan; Khaviar Warih Yumarestu (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
The involvement of Arabic literature in the development of Islamic da'wah broadcasting is an important element in understanding the history and development of da'wah in a global context. This journal aims to analyze the important role of Arabic literature in advancing and expanding the realm of broadcasting Islamic da'wah. This research uses a qualitative approach with literature analysis methods to find out the challenges of the role of Arabic literature in broadcasting Islamic da'wah amidst the dominance of English. The analysis involves the development of the role of Arabic literature in broadcasting Islamic da'wah in the modern era. The research results highlight the important contribution of Arabic literature to the development of the content of da'wah, the relevance of classical Islamic messages to modern contexts and examples of cases of transformation of Islamic da'wah messages through Arabic (khutbahs, books, social media). It turns out that Arabic literature is not only a source of inspiration, but also a guide in developing da'wah communication strategies that are relevant to the times. The involvement of Arabic literature in the development of Islamic da'wah broadcasting does not only involve theoretical aspects but also practical aspects in its implementation. The transformation of Islamic da'wah messages through Arabic, which has become the main source of reference in Islam, has helped shape narratives, depict core Islamic values, and facilitate various broadcasting efforts to reach a wider audience.